CLINICAL MANIFESTATIONS AND TREATMENT EFFICIENCY OF THOSE SUFFERING FROM TB/HIV CO -INFECTION AND HEPATITIS - T. Yu. SАLINА; T. I. MOROZOVА (Туберкулез и болезни лёгких)
Goal: to analyze clinical manifestations and treatment efficiency in those suffering from TB/HIV co-infection and chronic hepatitis.Materials and methods. Medical cards of 129 patients with TB/HIV co-infection treated in TB units of Saratov Region were retrospectively analyzed. Patients were divided into 2 groups: Group 1 included 27 patients with TB/HIV co-infection and chronic hepatites B, C and others, Group 2 included 102 patients with TB/HIV co-infection and without hepatitis.Results. It was found out that TB/HIV co-infection and hepatitis were the most often registered in the people from 41 to 55 years old, while the highest incidence of TB/HIV co-infection was observed in the younger people – from 21 to 40 years old. There was no significant difference in the clinical forms of tuberculosis, bacillary excretion and destruction of the lung tissue between the Groups. However, bacillary excretion was much more frequent compared to the level of destructive changes in the lungs in patients of both Groups. The patients with TB/HIV co-infection and hepatitis had a confidently higher level of MDR – 64.3% versus 17.3% in the patient with TB/HIV co-infection, which was especially high in the patients concurrently receiving anti-tuberculosis treatment and antiretroviral therapy (ART). The mortality related to HIV was the highest in the Group of patients with TB/HIV co-infection and hepatitis receiving no ART, which was 4 times higher than the same rate in TB/HIV patients without hepatitis.